2012
DOI: 10.3892/or.2012.1760
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a human compact anti-ErbB2 antibody on prostate cancer

Abstract: Abstract. Prostate cancer is the most commonly diagnosed malignancy in men in developed countries. ErbB2, a tyrosine kinase receptor overexpressed in many human cancer types, contributes to prostate cancer progression by activating the androgen receptor in a steroid poor environment, thus promoting androgen-independent cell growth. The consequent development of hormone refractory tumors is a major obstacle in prostate cancer therapy. The inhibition of ErbB2 signal transduction pathways by the use of human anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…A wave of preclinical and clinical studies showed the potential of developing treatment targeting TLRs against prostate cancer. Based on these researches, one of the most probable approaches is to use agents targeting TLRs as adjuvants along with other treatments (67, 68, 71, 77, 78). Above all, elucidation of the mechanisms of cancer cell TLR signaling and crosstalk with other signaling pathways as well as the mechanisms of cancer progression will definitely provide a promising novel strategy for cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A wave of preclinical and clinical studies showed the potential of developing treatment targeting TLRs against prostate cancer. Based on these researches, one of the most probable approaches is to use agents targeting TLRs as adjuvants along with other treatments (67, 68, 71, 77, 78). Above all, elucidation of the mechanisms of cancer cell TLR signaling and crosstalk with other signaling pathways as well as the mechanisms of cancer progression will definitely provide a promising novel strategy for cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Because Her-2 expression significantly differs between normal and tumor cells, the Her-2 protein has become an ideal target for immunotherapy 89…”
Section: Introductionmentioning
confidence: 99%